2020
DOI: 10.1016/j.labeco.2020.101849
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Cognitive Domains and the Returns to Schooling in South Africa: Evidence from Two Labor Surveys

Abstract: Numerous studies have considered the important role of cognition in estimating the returns to schooling. How cognitive abilities affect schooling may have important policy implications, especially in developing countries during periods of increasing educational attainment. Using two longitudinal labor surveys that collect direct proxy measures of cognitive skills, we study the importance of specific cognitive domains for the returns to schooling in two samples. We instrument for schooling levels and we find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…These findings highlight that perceived economic benefits play a pivotal role in driving the private demand for postgraduate studies within Kenyan universities. This aligns with the observations made by Nikolov et al (2020), who found that pursuing further education led to an increase in earnings by 18-20% in South Africa. Similarly, Netcoh (2016) advanced that education and training contribute to economic gains such as raised wages and an increase in domestic product.…”
Section: Integration Of Qualitative and Quantitative Findings On Perc...supporting
confidence: 92%
See 1 more Smart Citation
“…These findings highlight that perceived economic benefits play a pivotal role in driving the private demand for postgraduate studies within Kenyan universities. This aligns with the observations made by Nikolov et al (2020), who found that pursuing further education led to an increase in earnings by 18-20% in South Africa. Similarly, Netcoh (2016) advanced that education and training contribute to economic gains such as raised wages and an increase in domestic product.…”
Section: Integration Of Qualitative and Quantitative Findings On Perc...supporting
confidence: 92%
“…In South Africa, Nikolov et al (2020) revealed that each additional year of schooling leads to an increase in earnings ranging from 18 to 20 percent. Moreover, studies in the country have demonstrated that the benefits of higher education are on the rise, as advanced education empowers graduates to access higher-paying jobs and enhanced opportunities for career advancement (Salisbury, 2016;Horn, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Recap your core findings o Offer an intuitive and gripping account of these results o Compare your results to the existing literature and emphasize why the results are novel o Discuss the mechanisms driving your principal findings • Provide caveats and acknowledge significant limitations of your approach • Suggest promising avenues for future research • Explore potential policy implications Let's consider an example from Nikolov and Jimi (2020) and how their study on the returns to various cognitive skills for labor market outcomes in South Africa illustrates an effective conclusion section in light of the attributes just highlighted for an effective conclusion section. Here is the excerpt:…”
Section: A Main Elementsmentioning
confidence: 99%
“…Here is an example of how Nikolov and Jimi (2020) write up their concluding remarks in a study that examines the returns to cognitive skills for labor market outcomes in South Africa. Note each of the following:…”
Section: A Main Elementsmentioning
confidence: 99%